Non-Retinotopic Motor-Visual Recalibration to Temporal Lag - Tsujita, Masaki; Ichikawa, Makoto (Frontiers in Psychology, 2012)
Temporal order judgment between the voluntary motor action and its perceptual feedback is important in distinguishing between a sensory feedback which is caused by observer’s own action and other stimulus, which are irrelevant to that action. Prolonged exposure to fixed temporal lag between motor action and visual feedback recalibrates motor-visual temporal relationship, and consequently shifts the point of subjective simultaneity (PSS). Previous studies on the audio-visual temporal recalibration without voluntary action revealed that both low and high level processing are involved. However, it is not clear how the low and high level processings affect the recalibration to constant temporal lag between voluntary action and visual feedback. This study examined retinotopic specificity of the motor-visual temporal recalibration. During the adaptation phase, observers repeatedly pressed a key, and visual stimulus was presented in left or right visual field with a fixed temporal lag (0 or 200 ms). In the test phase, observers performed a temporal order judgment for observer’s voluntary keypress and test stimulus, which was presented in the same as or opposite to the visual field in which the stimulus was presented in the adaptation phase. We found that the PSS was shifted toward the exposed lag in both visual fields. These results suggest that the low visual processing, which is retinotopically specific, has minor contribution to the multimodal adaptation, and that the adaptation to shift the PSS mainly depends upon the high level processing such as attention to specific properties of the stimulus.